(untitled) (XXI Century. Spanish Literature and Culture, 2007)
In this article, the cultural and historical context into which the ¨micro story¨ bursts is expounded upon: a new literary genre sustained in the aesthetic of brevity and the ellipsis, which has reached spectacular development in the Hispanic world. After presenting its distinctive characteristics, the hyper-short stories of three masters of the genre in Spain are studied: Luis Mateo Díez, José Mª Merino y Juan Pedro Aparicio.